2013
DOI: 10.1371/journal.pone.0058891
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of COX-2 Immunohistochemical Expression in Colorectal Cancer: A Meta-Analysis of the Literature

Abstract: BackgroundCyclooxygenase-2 (COX-2) is believed to be an important enzyme in the pathogenesis of colorectal cancer (CRC). Correlations between the expression of COX-2 with tumor growth and distant metastasis have become an issue; thus, attention has been paid to COX-2 as a prognostic factor. Various studies examined the relationship between COX-2 immunohistochemistry (IHC) overexpression with the clinical outcome in patients with colorectal cancer, but yielded conflicting results. The prognostic significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 45 publications
1
41
0
2
Order By: Relevance
“…jci.org Volume 124 Number 11 November 2014 production (8). COX-2 expression is associated with poor patient prognosis and survival (33,34). We previously reported that, in addition to tumor COX-2 expression, COX-2 present in stromal tissues had a significant effect on tumor-associated angiogenesis (35).…”
Section: Resultsmentioning
confidence: 99%
“…jci.org Volume 124 Number 11 November 2014 production (8). COX-2 expression is associated with poor patient prognosis and survival (33,34). We previously reported that, in addition to tumor COX-2 expression, COX-2 present in stromal tissues had a significant effect on tumor-associated angiogenesis (35).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to that the majority of included publications found only an indeterminate association of COX and patient prognosis. Of note most studies comprised a mixture of primary CRC patients and no analysis on the prognostic role of COX-2 in pulmonary metastases (27). One has to be careful when transferring conclusions from primary tumors to metastasized tumor stages.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors which may be associated with COX-2 in breast cancer, which should be investigated in further studies. It is critical for breast cancer management to identify those biomarkers that would provide those factors potentially curable given the availability of early diagnosis and effective therapeutic protocols, at the time of diagnosis, a reliable prognostic assessment and prediction of treatment response (Thorat et al, 2013;Peng et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%